'All Impetuous Rage': The Cult of Waterfalls in Eighteenth-century Wales. (June 2014) - Hayman, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> Waterfalls became places of tourism and recreation in eighteenth-century Wales and by the heyday of the Celtic Tour at the end of the eighteenth century and the beginning of the nineteenth they had achieved a special status as one of the iconic features of the Welsh landscape. The article begins its discussion of waterfalls with the developing interest in natural scenery in Wales earlier in the eighteenth century, and demonstrates how waterfall scenery was incorporated into private parks. It then examines how waterfalls were sought out by travellers through North and South Wales, the consequence of which was that the waterfall became one of the chief aesthetic thrills of the period. Interest waned in the nineteenth century when waterfalls could no longer be relished as undiscovered and tourists were drawn further afield. Aesthetic attitudes also changed. The waterfall was no longer part of a social scene, nor was it viewed as a part of a harmonious landscape that contrasted rural with urban life. The waterfall became a work of nature in its own right.